Effectiveness of ultrasound algorithm in prenatal diagnosis of hemoglobin Bart's disease among pregnancies at risk. Issue 2 (26th February 2022) - Harn‐a‐morn, Panwad; Wanapirak, Chanane; Sirichotiyakul, Supatra; Srisupundit, Kasemsri; Tongprasert, Fuanglada; Luewan, Suchaya; Tongsong, Theera
Abstract: Objective: To evaluate the effectiveness of ultrasound algorithm in diagnosis of fetal Hb Bart's disease among pregnancies at risk. Methods: Pregnancies at risk underwent ultrasound for the first time at 12–14 weeks of gestation and serial ultrasound every 2–4 weeks until 24 weeks to identify pre‐hydropic signs. The invasive procedure was omitted in case of no pre‐hydropic signs. Results: A total of 237 fetuses were recruited, including 53 affected and 184 unaffected fetuses. The algorithm has a sensitivity of 100% in the detection of fetal Hb Bart's disease with a false positive rate of 10.9%. Of the affected group, the mean gestational age at the time of diagnosis was 15.5 ± 2.6 week. 30.8% of all pregnancies at risk underwent invasive procedures. The algorithm had a 70% reduction in the rate of invasive procedures among pregnancies at risk without missing the affected cases. Conclusions: The algorithm is highly effective in the early detection of fetal Hb Bart's disease with a detection rate of 100%, and invasive diagnosis can be avoided in about 70% of cases. Thus, this algorithm should be used as a guideline for prenatal diagnosis of fetal Hb Bart's disease, especially in geographical areas of high prevalence. Abstract : The algorithm is highly effective in early detection of fetal Hb Bart's disease with a detection rate of100% and the invasive diagnosis can be avoided in about 70% of cases.